Volcanoes buried in Te Riu-a-Māui/Zealandia sedimentary basins. Issue 4 (1st October 2020) - Bischoff, Alan; Barrier, Andrea; Beggs, Mac; Nicol, Andrew; Cole, Jim; Sahoo, Tusar
ABSTRACT: Many volcanoes are buried within Te Riu-a-Māui/Zealandia sedimentary basins. Based on a large collection of seismic reflection and drillhole data, this paper outlines the morphology, location and age of over 400 volcanoes buried and preserved in offshore New Zealand basins. We discuss the relationships of these volcanoes to the timing and locations of the main tectonic events that shaped Zealandia in the last 105 Myr. Late Cretaceous volcanism mainly formed large (>20 km 3 ) composite cones and volcanic complexes that erupted along rift faults related to the break-up of Zealandia from south-eastern Gondwana. Cenozoic intraplate volcanic activity was widespread, typically forming clusters of scattered small-volume (<1 km 3 ) craters and cones. In contrast, large Cenozoic volcanic complexes, composite cones and shield volcanoes erupted along linear arcs associated with subduction along the Pacific-Australian plate boundary. In detail, the presence of pre-existing structures and types of host rocks also influence the passage of magma in the shallow (<5 km) crust and the location of eruptive centres, regardless the tectonic setting of eruption. Insights from this work demonstrate the value of characterising volcanoes buried in sedimentary basins for improved understanding of the interplay between volcanism and plate tectonics in Zealandia and further afield.